Globalization and Islamic Educational Challenges: Views from East Javanese Pesantren - KAWAKIP, Akhmad Nurul (Ulumuna, 2020)
There have been social, political and religious changes in Indonesia since the fall of the New Order regime in 1998. Globalization has furthered acceleration of the change. These forces have given tremenduous impacts on Indonesian educational system, and Islamic educational system (pesantren) in particular. This article examines how pesantrens respond globalization and explores what pesantrens have developed during the era. Based on an ethnographic study in pesantrens in East Java, this study explores the conception, policy and practices of Islamic education in the pesantren in this globalization era. It argues that globalization increases the complexity and the necessity of learning and teaching development, particularly in preparing students (santri) to deal with the challenges of rapid growth and change of contemporary world. The responses of pesantren on global challenges have been shown through the development of its traditional system, namely curricula development and leadership. The new pesantren educational system, management and leadership are now sustainable and relevant to the modern world. The shifting educational paradigm in the pesantren’s policy supports Sadalah’s and Hefner’s contention that the Islamic educational system in the contemporary era needs to adopt, accept and integrate the teaching content of non-traditional Islamic subjects into their programs.